A new species of Terriera from Guizhou Province, China - Cheng, Yuan-Hui; Guo, Mei-Jun; Hou, Cheng-Lin (Phytotaxa, 2024)
Specimens of Terriera collected from dead leaves of woody plant in the Fodingshan National Nature Reserve, Guizhou Province, China, were identified as a new species and named Terriera tongrenensis. Multi-gene phylogenetic analyses based on ITS-nrLSU-mtSSU show that T. tongrenensis clusters with other Terriera species and is closely related to Terriera houjiazhuangensis, Terriera guizhouensis, Terriera pandanicola, and Terriera sigmoideospora. Morphological comparison reveals distinct differences between the new species and its relatives. T. tongrenensis has the ascomata on abaxial surface of dead leaves, the covering stroma consisting of an innermost layer with a few thin-walled, hyaline, angular to globose cells near the opening and extending to the basal stroma, the absence of an excipulum and the internal matrix of stroma. These findings highlight the unique characteristics of T. tongrenensis, reinforcing its status as a distinct species within the genus.